Rehabilitation of the Upper Limb After Radical Mastectomy: A Literature Review - Kociucka, Patrycja; Sadowski, Krzysztof; Modelska, Julia; Jeleń, Anita; Podolska, Anna; Paluchowicz, Karolina; Siwicka, Katarzyna; Szewczyk, Konrad; Janasik, Laura (Quality in Sport, 2026)
Background: Radical mastectomy often results in upper extremity complications, including shoulder impairment, pain, reduced range of motion, lymphedema, and diminished muscle strength, which significantly impact quality of life. Key risk factors include extent of lymph node dissection, older age, and axillary radiation, exacerbating morbidity. Aim: This review synthesizes current literature on upper extremity complications post-radical mastectomy and evaluates the effectiveness of rehabilitation strategies. Material and methods: A comprehensive search of PubMed, PEDro, and Scopus identified English-language studies from the last decade on shoulder impairment in adult women post partial or total mastectomy for breast cancer. Results: Complications are highly prevalent, with rehabilitation interventions demonstrating efficacy in improving shoulder function, reducing pain and lymphedema. Challenges persist due to heterogeneous protocols and limited high-quality trials. Conclusions: Targeted rehabilitation interventions post-radical mastectomy significantly improve shoulder function, range of motion, muscle strength, and reduce pain and lymphedema incidence, thereby enhancing quality of life and functional independence (Marco et al., 2023; Xu et al., 2024; Zhang et al., 2022). Despite these demonstrated benefits from early exercises and structured programs (Lazaraviciute & Chaturvedi, 2017; Naqvi, 2021), heterogeneous protocols, paucity of high-quality randomized trials, and variability due to risk factors like axillary dissection and radiation underscore the urgent need for standardized guidelines and further large-scale RCTs (Bruce et al., 2021).